The Effectiveness of Using Youtube in Basic Chemistry Practicum Courses in Digital-Based Learning to increase Student Creativity: - Anita Debora Simangunsong; Febri Yanti (Jurnal Mantik, 2022)
The study aimed to determine the effectiveness of using Youtube in basic chemistry practicum courses in digital-based learning to increase student creativity. The subjects of this study were students of the chemical education study program, totaling 15 students. Data collection techniques used are tests, observations, and documentation. The data analysis technique was carried out in a quantitative descriptive manner. The research was carried out in two cycles. The results showed that there was an increase in learning outcomes and also student creativity in the use of Youtube in basic chemistry practicum courses. Learning outcomes in the first cycle the average value is 74.73. These results still do not meet the mastery value of the basic chemistry practicum course, which is 75. Then proceed to cycle II which has an average value of 85.53. The results in the second cycle stated that the average value had reached completeness or graduation in the basic chemistry practicum course, which was 85.53. Thus, an increase in the average value from cycle I to cycle II of 14.45% states that the use of youtube in basic chemistry practicum courses in digital-based learning is effective in improving student learning outcomes. Based on observational data, it is stated that the use of YouTube in the Basic Chemistry Practicum in Digital-Based Learning is effective for increasing Creativity.